1995
DOI: 10.1111/j.1476-5381.1995.tb14998.x
|View full text |Cite
|
Sign up to set email alerts
|

D‐Cycloserine transport in human intestinal epithelial (Caco‐2) cells: mediation by a H + ‐coupled amino acid transporter

Abstract: Medical School, Newcastle upon Tyne, NE2 4HH1 The ability of D-cycloserine to act as a substrate for H+/amino acid symport has been tested in epithelial layers of Caco-2 human intestinal cells. 2 In Na+-free media with the apical bathing media held at pH 6.0, D-cycloserine (20 mM) is an effective inhibitor of net transepithelial transport (Jnet) of L-alanine (100 pM) and its accumulation (across the apical membrane) in a similar manner to amino acid substrates (L-alanine, /3-alanine, L-proline and glycine). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
(43 reference statements)
1
38
0
Order By: Relevance
“…This amino acid transport is coupled with proton inflow in monolayers of Caco-2 cells that have been loaded with the pH-sensitive fluorescent dye BCECF (BCECF; refs. 7,8). These observations emphasize the potential importance of the H + electrochemical gradient as a driving force of solute absorption across the mammalian intestinal wall.…”
Section: Introductionmentioning
confidence: 69%
“…This amino acid transport is coupled with proton inflow in monolayers of Caco-2 cells that have been loaded with the pH-sensitive fluorescent dye BCECF (BCECF; refs. 7,8). These observations emphasize the potential importance of the H + electrochemical gradient as a driving force of solute absorption across the mammalian intestinal wall.…”
Section: Introductionmentioning
confidence: 69%
“…Although direct measurement of transepithelial transport of vigabatrin is necessary to verify that vigabatrin exits the basolateral membrane of these intestinal epithelial cells, previous investigations with other PAT1 substrates, namely β ‐alanine, L ‐alanine, α ‐methylaminoisobutyric acid, proline, GABA and glycine ( Thwaites et al ., 1993a , 1993b ; 1994 ; 1995a , 1995b , 1995c ; 2000 ), when considered alongside the high oral bioavailability of vigabatrin, suggest that transepithelial transport occurs. Potential efflux systems localised to the basolateral membrane of the small intestine include system L (CD98/LAT2, SLC3A2/SLC7A8) which exchanges neutral amino acids ( Rossier et al ., 1999 ; Bauch et al ., 2003 ), system y + L (CD98/y + LAT1, SLC3A2/SLC7A7), which exchanges neutral amino acids for intracellular cationic amino acids in the presence of sodium ( Kanai et al ., 2000 ; Bauch et al ., 2003 ), or system asc (CD98/asc1, SLC3A2/SLC7A10), which is a Na + ‐independent, high‐affinity neutral amino‐acid exchanger ( Wagner et al ., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of hPAT1 substrate specificity have confirmed these earlier reports which showed that hPAT1 may play a unique role in the small intestine by acting as the only high‐capacity mechanism for uptake of the conditionally essential amino acid taurine and neuroactive D ‐amino acids such as D ‐serine (Thwaites et al, 1995b; Thwaites and Stevens, 1999; Chen et al, 2003). hPAT1 transports potential therapeutic compounds such as D ‐cycloserine and betaine (Thwaites et al, 1995a,b; Boll et al, 2003; Anderson et al, 2004). Recently, it has been identified that PAT1 can also transport short chain fatty acids such as butyrate (Foltz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Details of what happens to hPAT1‐mediated amino acid absorption during such disease states has yet to be studied in detail but we would suggest that excessive VIP would exacerbate the generalised mal‐absorption associated with diarrhoea due to downregulation of pro‐absorptive mechanisms involved in both nutrient and salt absorption. Inhibition of hPAT1 by VIP in such situations would result in malabsorption of not only essential amino acids but also a number of therapeutic agents such as D ‐cycloserine (used as an antibiotic) (Thwaites et al, 1995a). This may be particularly significant in infant diarrhoea where the potential for mal‐absorption of dietary taurine [a hPAT1 substrate (Thwaites and Stevens, 1999)] may have prominent effects on development (Sturman, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation